Toward target search approach of swarm robotics in limited communication environment based on robot chains with elimination mechanism. (21st May 2020) - Luo, Yandong; Guo, Jianwen; Ye, Guoliang; Wang, Yan; Xie, Li; Wang, Xiang; Zhang, Shaohui; Yan, Xiaohui
Swarm robotics refers to artificial swarm systems composed of a large number of autonomous mobile robots with relatively simple structures and functions. One of the basic problems of swarm robotics involves the target search process, which entails a cooperative search using limited perception and local interaction of robots under a self-organizing mechanism. When communication is limited, the connectivity of swarm robotics may decrease, leading to the failure of the target search task. This article describes a new target search method based on the robot chain model and the elimination mechanism. The proposed method allows the target search task to be completed efficiently and reliably while maintaining the connectivity of the robots. Experimental results show that the proposed algorithm offers better performance than conventional techniques in terms of search speed and success rate, and provides an effective method for solving the target search problem using swarm robotics in limited-communication environments.